FungalRoot: global online database of plant mycorrhizal associations. Issue 3 (20th May 2020) - Soudzilovskaia, Nadejda A.; Vaessen, Stijn; Barcelo, Milagros; He, Jinhong; Rahimlou, Saleh; Abarenkov, Kessy; Brundrett, Mark C.; Gomes, Sofia I.F.; Merckx, Vincent; Tedersoo, Leho
Summary: Testing of ecological, biogeographical and phylogenetic hypotheses of mycorrhizal traits requires a comprehensive reference dataset about plant mycorrhizal associations. Here we present a database, FungalRoot, which summarizes publicly available data about vascular plant mycorrhizal type and intensity of root colonization by mycorrhizal fungi, accompanied with rich metadata. We compiled and digitized data about plant mycorrhizal colonization in nine widespread languages. The present version of the FungalRoot database contains 36 303 species‐by‐site observations for 14 870 plant species, tripling the previously available compiled information about plant mycorrhizal associations. Based on these data, we provide a recommended list of genus‐level plant mycorrhizal associations, based on the majority of data for species and careful analysis of conflicting data. The majority of ectomycorrhizal and ericoid mycorrhizal plants are trees (92%) and shrubs (85%), respectively. The majority of arbuscular and nonmycorrhizal plant species are herbaceous (50% and 70%, respectively). Our publicly available database is a powerful resource for mycorrhizal scientists and ecologists. It features possibilities for dynamic updating and addition of data about plant mycorrhizal associations. The new database will promote research on plant and fungal biogeography and evolution, and on links between above‐ and belowground biodiversity and ecosystem functioning.